Private and Public Education in Kenya: the Case of Strathmore College - Carlos Sotz (Universidad de Navarra, 2018)
After Independence the Kenya Government decided to shape one nation by removing racial discrimination from the education system and providing equal opportunities to all; this was achieved by transferring the management of all secondary schools and colleges to Boards of Governors and giving them Grant-in-aid status. To keep its autonomy Strathmore College opted to operate privately. The integration of the education system enhanced certain human rights but diminished religious freedom. The experience of Strathmore College shows that Boards of Governors and Sponsors may need more freedom to discharge their responsibilities.